Chilean swallows (Tachycineta meyeni) adjust the number of feathers added to the nest with time of breeding - Liljesthrom, Marcela (2009)
Tachycineta swallows nest in secondary cavities and build nests made of a mat of dry grasses with a nest cup lined with feathers. The insulative quality of feathers may prevent hypothermia of the chicks and increase chick growth, but also may raise the risk of nestling hyperthermia if ambient temperature is high. The number of feathers added to the nest should vary throughout the breeding season according to ambient temperature. We describe nest structure and timing of nest building of Chilean Swallows (Tachycineta meyeni) nesting in Tierra del Fuego, Argentina. We analyzed the association between number of feathers in the nest and (1) daily ambient temperature during the period swallows add feathers to the nest, and (2) hatching success of eggs and survival and growth of the chicks. There was a negative association between number of feathers added to the nest and average daily ambient temperature during the nesting cycle. Hatching success was not associated with number of feathers at start of laying or at the end of incubation. There was no association between number of feathers and chick survival or between number of feathers and average weight of the chicks when they were 12 and 15 days of age. Chilean Swallows make temporal adjustments to the number of feathers added to the nest. We suggest these adjustments may help maintain reproductive success throughout the breeding season.